2021
DOI: 10.1002/jat.4170
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress‐mediated apoptosis is involved in bisphenol S‐induced reproductive toxicity in male C57BL/6 mice

Abstract: The reproductive toxicity of bisphenol S (BPS) in male mammals and its possible mechanism are not clear. We investigated the effects and possible mechanism of action of BPS on adult male C57BL/6 mice. We found that exposure to 200‐mg/kg BPS resulted in a significant decrease in the sperm count in the caput/corpus and cauda epididymis, significantly decreased sperm motility, and significantly increased the sperm deformity. Histological evaluation revealed that BPS exposure caused a decrease of spermatozoa in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Our early research indicated that BPS can cause a reduction in SOD and GSH‐Px activities as well as glutathione levels in the testis of mice, which is accompanied by an increase in the end product of lipid peroxide malondialdehyde. [ 20 ] This observation suggests the induction of oxidative stress by BPS in mouse testicular tissue. Here, we further investigated whether BPS could induce oxidative stress in testicular tissue by inhibiting the Nrf2/HO‐1 signaling pathway.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our early research indicated that BPS can cause a reduction in SOD and GSH‐Px activities as well as glutathione levels in the testis of mice, which is accompanied by an increase in the end product of lipid peroxide malondialdehyde. [ 20 ] This observation suggests the induction of oxidative stress by BPS in mouse testicular tissue. Here, we further investigated whether BPS could induce oxidative stress in testicular tissue by inhibiting the Nrf2/HO‐1 signaling pathway.…”
Section: Discussionmentioning
confidence: 88%
“…The dose chosen was based on our previous study. [ 20 ] The mice from each group were killed on the 29th day after treatment. The blood was collected and centrifuged at 1000 g for 10 min; then, the serum was stored at −20°C until enzyme‐linked immunosorbent assay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic pathway proapoptotic proteins Bcl‐2‐associated X protein (Bax) and cysteinyl aspartate specific proteinase 3 (Caspase3) lie upstream of mitochondrial oxidative stress‐inducing activity, and also play a vital role in the generation of oxidative stress in adult mouse organs 21 . Bisphenol S exposure can cause oxidative stress and apoptosis in spermatogenic cells 22 . Oxidative stress‐induced cardiomyocyte apoptosis through abnormalities in the Akt/p53 signaling pathway 23 .…”
Section: Introductionmentioning
confidence: 99%
“…21 Bisphenol S exposure can cause oxidative stress and apoptosis in spermatogenic cells. 22 Oxidative stress-induced cardiomyocyte apoptosis through abnormalities in the Akt/p53 signaling pathway. 23 The research by Ren et al has shown that oxidative stress can induce apoptosis by destroying mitochondrial structure, and the onset of type 2 diabetes is related to its damage to the normal function of islet β cells.…”
Section: Introductionmentioning
confidence: 99%